Transcriptome-Based Network Analysis Reveals Hirudin Potentiates Anti-Renal Fibrosis Efficacy in UUO Rats - Yu, Hang-Xing; Lin, Wei; Yang, Kang; Wei, Li-Juan; Chen, Jun-Li; Liu, Xin-Yue; Zhong, Ke; Chen, Xin; Pei, Ming; Yang, Hong-Tao (Frontiers in Pharmacology, 2021)
Background:Hirudin has been widely used in the treatment of antifibrosis. Previous studies have shown that hirudin can effectively improve the clinical remission rate of chronic kidney disease. However, the mechanism of its renal protection has not been systematically investigated. Methods:In this study, the reliability of UUO-induced renal interstitial fibrosis was evaluated by histopathological verification. High-throughput transcriptome sequencing was used to elucidate the molecular mechanism of hirudin, differentially expressed mRNAs were identified, and their functions were analyzed by GO analysis and GSEA. In addition, the RNA-seq results were validated by in vitro and vivo experiments. Results:We found 322 identical differential expressed genes (IDEs) in the UUO hirudin-treated group compared with the sham group. Functional enrichment analysis indicated that cellular amino acid metabolic processes were the most obvious enrichment pathways in biological processes. In terms of molecular functional enrichment analysis, IDEs were mainly enriched in coenzyme binding, pyridoxal phosphate binding and other pathways. In addition, microbody is the most obvious pathway for cellular components. A total of 115 signaling pathways were enriched, and AMPK, JAK-STAT and PI3K-Akt signaling pathways were the important signaling pathways enriched. We found that PI3K, p-Akt, and mTOR expression were significantly reduced by hirudin treatment. In particular, our results showed that hirudin could induce a decrease in the expression of autophagy-related proteins such as P62, LC3, Beclin-1 in TGF-β1-induced NRK-52E cells. Conclusion:Our results suggest that hirudin may protect the kidney by ameliorating renal autophagy impairment through modulating the PI3K/Akt pathway.